2018
DOI: 10.1002/bsl.2388
|View full text |Cite
|
Sign up to set email alerts
|

Justice at any cost? The impact of cost–benefit salience on criminal punishment judgments

Abstract: This study investigated the effect of cost–benefit salience on simulated criminal punishment judgments. In two vignette‐based survey experiments, we sought to identify how the salience of decision costs influences laypeople's punishment judgments. In both experiments (N1 = 109; N2 = 398), undergraduate participants made sentencing judgments with and without explicit information about the direct, material costs of incarceration. Using a within‐subjects design, Experiment 1 revealed that increasing the salience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 60 publications
(80 reference statements)
1
14
0
Order By: Relevance
“…Our pattern of results aligns closely with other research, including studies of sentencing attitudes [18][19][20][21]38], showing that cost prompts can induce people to trade off these so-called sacred values [39]. The present results extend these previous findings by demonstrating that the effect of cost-benefit salience on punishment judgments may be specific to costs and may represent an implicit effect of cognitive availability, as opposed to a calculated response to gaining new insight about the costs of incarceration.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our pattern of results aligns closely with other research, including studies of sentencing attitudes [18][19][20][21]38], showing that cost prompts can induce people to trade off these so-called sacred values [39]. The present results extend these previous findings by demonstrating that the effect of cost-benefit salience on punishment judgments may be specific to costs and may represent an implicit effect of cognitive availability, as opposed to a calculated response to gaining new insight about the costs of incarceration.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, our conclusions are limited by the type of crime examined, namely drug trafficking. Previous research has found similar effects of cost information using cases of aggravated robbery and home invasion [20,21]. We do not necessarily expect punishers to consider the costs of incarceration for the most serious crimes, such as murder, even after being prompted.…”
Section: Limitations and Future Directionsmentioning
confidence: 74%
See 2 more Smart Citations
“…Such a neglect of long-term effects of decisions has also been found in punishment behavior. For example, recent research has shown that individuals generally do not incorporate the costs of incarceration into their punishment preferences, unless information about such costs is made explicitly salient (Aharoni, Kleider-Offutt, Brosnan, & Watzek, 2018). Given that the support for utilitarian punishment requires, by definition, a forward-oriented thinking about punishment (i.e., taking long-term effects into account), punishers may only consider pursuing such punishment goals if information related to utilitarian aspects of the crime situation is salient.…”
Section: Information Salience and Laypeople's Punishment Goalsmentioning
confidence: 99%